A new species of Agathirsia Westwood (Hymenoptera: Braconidae: Agathidinae) from Mexico - Sharkey, Michael J. (Zootaxa, 2005)
A remarkable new species of Agathirsia is described. Unlike all other species of Agathirsia, and most other Agathidinae, it lacks pegs or thick spines at the apex of the hind tibia. The only other genus of Agathidinae with this characteristic is Crassomicrodus, and the new species’ potential affinities with members of Crassomicrodus are discussed.